Experimental Study on Axial Impact Mitigating Stick-Slip Vibration with a PDC Bit - Yong Wang; Hongjian Ni; Yiliu (Paul) Tu; Ruihe Wang; Xueying Wang; Heng Zhang; Jiaxue Lyu; Hongqiao Xie (Shock and Vibration)
Stick-slip vibration reduces the drilling rate of penetration, causes early wear of bits, and threatens the safety of downhole tools. Therefore, it is necessary to study suppression methods of stick-slip vibration to achieve efficient and safe drilling. Field tests show that the use of downhole axial impactors is helpful to mitigate stick-slip vibration and improve rock-breaking efficiency. However, there are many deficiencies in the study of how axial impact load affects stick-slip vibration of a PDC bit. In this paper, based on the two-degrees-of-freedom spring-mass-damper model and similarity theory, a laboratory experiment device for suppressing stick-slip vibration of a PDC bit under axial impact load has been developed, and systematic experimental research has been carried out. The results show that the axial impact force can suppress the stick-slip vibration by reducing the amplitude of weight on bit and torque fluctuations and by increasing the main frequency of torque. The amplitude of impact force affects the choice of the optimal back-rake angle. The impact frequency is negatively correlated with the fluctuation amplitude of the rotary speed. When the impact frequency is greater than 100 Hz, the fluctuation amplitude of the rotary speed will not decrease.